The Forkhead Transcription Factor, FOXP3: A Critical Role in Male Fertility in Mice. Issue 1 (1st January 2014) - Jasurda, Jake S.; Jung, Deborah O.; Froeter, Erin D.; Schwartz, David B.; Hopkins, Torin D.; Farris, Corrie L.; McGee, Stacey; Narayan, Prema; Ellsworth, Buffy S.
Abstract: Fertility is dependent on the hypothalamic-pituitary-gonadal axis. Each component of this axis is essential for normal reproductive function. Mice with a mutation in the forkhead transcription factor gene, Foxp3, exhibit autoimmunity and infertility. We have previously shown that Foxp3 mutant mice have significantly reduced expression of pituitary gonadotropins. To address the role of Foxp3 in gonadal function, we examined the gonadal phenotype of these mice. Foxp3 mutant mice have significantly reduced seminal vesicle and testis weights compared with Foxp3 +/Y littermates. Spermatogenesis in Foxp3 mutant males is arrested prior to spermatid elongation. Activation of luteinizing hormone signaling in Foxp3 mutant mice by treatment with human chorionic gonadotropin significantly increases seminal vesicle and testis weights as well as testicular testosterone content and seminiferous tubule diameter. Interestingly, human chorionic gonadotropin treatments rescue spermatogenesis in Foxp3 mutant males, suggesting that their gonadal phenotype is due primarily to a loss of pituitary gonadotropin stimulation rather than an intrinsic gonadal defect.